Water Solubilization Using Nonionic Surfactants from Renewable Sources in Microemulsion Systems - Szumała, Patrycja (Springer-Verlag, 2012)
In this study the effect of temperature, NaCl and oils (hydrocarbons: C(8)–C(16)) on the formation and solubilization capacity of the systems of oil/monoacylglycerols (MAG):ethoxylated fatty alcohols (CEO(20))/propylene glycol (PG)/water was investigated. The effects of the surfactant mixture on the phase behavior and the concentration of water or oil in the systems were studied at three temperatures (50, 55, 60 °C) and with varied NaCl solutions (0.5; 2; 11%). Electrical conductivity measurement, FTIR spectroscopy and the DSC method were applied to determine the structure and type of the microemulsions formed. The dimension of the microemulsion droplets was characterized by dynamic light scattering. It has been stated that the concentration of CEO(20) has a strong influence on the shape and extent of the microemulsion areas. Addition of a nonionic surfactant to the mixture with MAG promotes an increase in the area of microemulsion formation in the phase diagrams, and these areas of isotropic region did not change considerably depending on the temperature, NaCl solution and oil type. It was found that, depending on the concentration of the surfactant mixture, it was possible to obtain U-type microemulsions with dispersed particles size distribution ranging from 25 to 50 nm and consisting of about 30–32% of the water phase in the systems. The conditions under which the microemulsion region was found (electrolyte and temperature—insensitive, comparatively low oil and surfactant concentration) could be highly useful in detergency.